Differential impact of acidic and alkaline conditions on hydrothermal pretreatment, fermentation and anaerobic digestion of sludge. (11th November 2022) - Kakar, Farokh Laqa; Liss, Steven N.; Elbeshbishy, Elsayed
Abstract: Anaerobic digestion and fermentation processes in wastewater sludge treatment are limited by several factors, including the slow breakdown of complex organic matter and solubilization of solids. In this study, thermochemical pretreatment of thickened waste activated sludge using high temperature (>170 °C) was investigated to understand the impact of the pretreatment on the volatile fatty acids (VFA) production and its fractions during the fermentation process. Furthermore, the influence the thermochemical pretreatment on sludge disintegration and methane recovery was investigated. A range of acidic and alkaline conditions over the pH range of 4.5–10 was examined. Sludge (pH adjusted) was exposed to hydrothermal pretreatment (HTP) at a temperature of 170 °C for 30 min. Pretreated samples were then subjected to batch fermentation and methane potential tests which revealed that acidic and alkaline conditions resulted in increased sludge solubilization during HTP. Acidic conditions were associated with a higher VFA production yield of up to 185 mg chemical oxygen demand/g total chemical oxygen demand. Alkaline conditions led to a higher methane production yield where the maximum yield (276 mL CH4 /g total chemical oxygen demandadded ) was found to occur at pH 10. Therefore, alkaline sludge used for fermentation has shown technical and economic feasibility for sludge carbon recovery. HIGHLIGHTS: Effect of pH on thermal pretreatment, fermentation and digestion was investigated. Acidic and alkaline pH had positive effect on thermal pretreatment performance. Acidic conditions resulted in higher volatile fatty acids production. Alkaline conditions resulted in higher methane production. Graphical Abstract